PERAN SERTA ORANG TUA DALAM SISTEM BUDAYA MUTU DI SEKOLAH DASAR PSKD MANDIRI - DWI RAHAYU (Jurnal Manajemen Pendidikan, 2016)
The objective of this research is to gain a deep understanding of the parents involvement in a quality culture system in PSKD MANDIRI Primary School. This research is a case study method. The validity of qualitative data obtained through the extention of time doing research and triangulation of data collection techniques and data sources in the field. The result show: Interpersonal communication in PSKD Mandiri Schools is the result of a good engagement between teachers and parents. Parents understand the procedures how to make a contact with teachers. Parents are also free to choose the communication channel that they desired. Schools encourage the use of technology in the communication between home – school. Several form of written communication have been considered including handbooks, newsletter, progress reports and home – school diaries. Guidelines have been also provided for the use of telephone contacts with parents and for the use of new technological option such as school website, e-mail, ans text messaging. Therefore, it is considered that making a range of strategies available to parents will lead to optional levels of parental involvement in school. However the range of strategies used by the school will mostly be dependent on teachers’s knowledge of and skills for effectively implementing the various strategies. The wide range of activities is also used by school to bring about high levels of parental involvement.